Effects of the UV Filter Octocrylene and Its Degradation Product Benzophenone on Pacific Oyster (Magallana gigas) Larvae: A Call for Reassessment of Environmental Hazards - Ana Carvalhais; Romina Lippa; Isabel Benta Oliveira; Gaetano Di Lorenzo; Cláudia Mieiro; Mário Pacheco (Toxics, 2025)
Early life stages are pivotal to the functioning and resilience of ecological systems, displaying heightened vulnerability to environmental changes and exposure to contaminants. Octocrylene (OC), an organic ultraviolet (UV) filter, and its breakdown product benzophenone (BP) are commonly found in aquatic environments, but their impact on keystone processes determining the success or failure of the early life stages of marine organisms remains underexplored. This study aims to assess the impacts of OC and BP at environmentally realistic concentrations (1, 10, and 100 µg.L−1), over a 24 h exposure period, on larvae of the Pacific oyster (Magallana gigas). A multiparametric approach was employed, examining DNA integrity, embryo–larval development and swimming velocity. The results showed that DNA integrity and swimming velocity were not affected by OC or BP; however, both compounds increased developmental abnormalities in D-shaped larvae in all concentrations tested. Considering the robustness of morphological parameters, often assumed as irreversible, and their critical influence on larvae survival, these findings suggest that environmentally relevant concentrations of OC and BP may threaten the success of oyster larvae, potentially impacting the population’s long-term stability and, ultimately, raising ecological health issues.